The PLATO mission - Rauer H.; Aerts C.; Cabrera J.; Deleuil M.; Erikson A.; Gizon L.; Goupil M.; Heras A.; Walloschek T.; Lorenzo-Alvarez J.; Marliani F.; Martin-Garcia C.; Mas-Hesse J.M.; O’Rourke L.; Osborn H.; Pagano I.; Piotto G.; Pollacco D.; Ragazzoni R.; Ramsay G.; Udry S.; Appourchaux T.; Benz W.; Brandeker A.; Güdel M.; Janot-Pacheco E.; Kabath P.; Kjeldsen H.; Min M.; Santos N.; Smith A.; Suarez J.-C.; Werner S.C.; Aboudan A.; Abreu M.; Acuña L.; Adams M.; Adibekyan V.; Affer L.; Agneray F.; Agnor C.; Aguirre Børsen-Koch V.; Ahmed S.; Aigrain S.; Al-Bahlawan A.; Alcacera Gil M.D.L.A.; Alei E.; Alencar S.; Alexander R.; Alfonso-Garzón J.; Alibert Y.; Allende Prieto C.; Almeida L.; Alonso Sobrino R.; Altavilla G.; Althaus C.; Alvarez Trujillo L.A.; Amarsi A.; Ammler-von Eiff M.; Amôres E.; Andrade L.; Antoniadis-Karnavas A.; António C.; Aparicio del Moral B.; Appolloni M.; Arena C.; Armstrong D.; Aroca Aliaga J.; Asplund M.; Audenaert J.; Auricchio N.; Avelino P.; Baeke A.; Baillié K.; Balado A.; Ballber Balagueró P.; Balestra A.; Ball W.; Ballans H.; Ballot J.; Barban C.; Barbary G.; Barbieri M.; Barceló Forteza S.; Barker A.; Barklem P.; Barnes S.; Barrado Navascues D.; Barragan O.; Baruteau C.; Basu S.; Baudin F.; Baumeister P.; Bayliss D.; Bazot M.; Beck P.G.; Belkacem K.; Bellinger E.; Benatti S.; Benomar O.; Bérard D.; Bergemann M.; Bergomi M.; Bernardo P.; Biazzo K.; Bignamini A.; Bigot L.; Billot N.; Binet M.; Biondi D.; Biondi F.; Birch A.C.; Bitsch B.; Bluhm Ceballos P.V.; Bódi A.; Bognár Z.; Boisse I.; Bolmont E.; Bonanno A.; Bonavita M.; Bonfanti A.; Bonfils X.; Bonito R.; Bonomo A.S.; Börner A.; Boro Saikia S.; Borreguero Martín E.; Borsa F.; Borsato L.; Bossini D.; Bouchy F.; Boué G.; Boufleur R.; Boumier P.; Bourrier V.; Bowman D.M.; Bozzo E.; Bradley L.; Bray J.; Bressan A.; Breton S.; Brienza D.; Brito A.; Brogi M.; Brown B.; Brown D.J.A.; Brun A.S.; Bruno G.; Bruns M.; Buchhave L.A.; Bugnet L.; Buldgen G.; Burgess P.; Busatta A.; Busso G.; Buzasi D.; Caballero J.A.; Cabral A.; Cabrero Gomez J.-F.; Calderone F.; Cameron R.; Cameron A.; Campante T.; Campos Gestal N.; Canto Martins B.L.; Cara C.; Carone L.; Carrasco J.M.; Casagrande L.; Casewell S.L.; Cassisi S.; Castellani M.; Castro M.; Catala C.; Catalán Fernández I.; Catelan M.; Cegla H.; Cerruti C.; Cessa V.; Chadid M.; Chaplin W.; Charpinet S.; Chiappini C.; Chiarucci S.; Chiavassa A.; Chinellato S.; Chirulli G.; Christensen-Dalsgaard J.; Church R.; Claret A.; Clarke C.; Claudi R.; Clermont L.; Coelho H.; Coelho J.; Cogato F.; Colomé J.; Condamin M.; Conde García F.; Conseil S.; Corbard T.; Correia A.C.M.; Corsaro E.; Cosentino R.; Costes J.; Cottinelli A.; Covone G.; Creevey O.L.; Crida A.; Csizmadia S.; Cunha M.; Curry P.; da Costa J.; da Silva F.; Dalal S.; Damasso M.; Damiani C.; Damiani F.; das Chagas M.L.; Davies M.; Davies G.; Davies B.; Davison G.; de Almeida L.; de Angeli F.; de Barros S.C.C.; de CastroLeão I.; de Freitas D.B.; de Freitas M.C.; De Martino D.; de Medeiros J.R.; de Paula L.A.; de Pedraza Gómez Á.; de Plaa J.; De Ridder J.; Deal M.; Decin L.; Deeg H.; Degl’Innocenti S.; Deheuvels S.; del Burgo C.; Del Sordo F.; Delgado-Mena E.; Demangeon O.; Denk T.; Derekas A.; Desert J.-M.; Desidera S.; Dexet M.; Di Criscienzo M.; Di Giorgio A.M.; Di Mauro M.P.; Diaz Rial F.J.; Díaz-García J.-J.; Dima M.; Dinuzzi G.; Dionatos O.; Distefano E.; do Nascimento Jr J.-D.; Domingo A.; D’Orazi V.; Dorn C.; Doyle L.; Duarte E.; Ducellier F.; Dumaye L.; Dumusque X.; Dupret M.-A.; Eggenberger P.; Ehrenreich D.; Eigmüller P.; Eising J.; Emilio M.; Eriksson K.; Ermocida M.; Escate Giribaldi R.I.; Eschen Y.; Espinosa Yáñez L.; Estrela I.; Evans D.W.; Fabbian D.; Fabrizio M.; Faria J.P.; Farina M.; Farinato J.; Feliz D.; Feltzing S.; Fenouillet T.; Fernández M.; Ferrari L.; Ferraz-Mello S.; Fialho F.; Fienga A.; Figueira P.; Fiori L.; Flaccomio E.; Focardi M.; Foley S.; Fontignie J.; Ford D.; Fornazier K.; Forveille T.; Fossati L.; Franca R.D.M.; Franco da Silva L.; Frasca A.; Fridlund M.; Furlan M.; Gabler S.-M.; Gaido M.; Gallagher A.; Gallego Sempere P.I.; Galli E.; García R.A.; García Hernández A.; Garcia Munoz A.; García-Vázquez H.; Garrido Haba R.; Gaulme P.; Gauthier N.; Gehan C.; Gent M.; Georgieva I.; Ghigo M.; Giana E.; Gill S.; Girardi L.; Giuliatti Winter S.; Giusi G.; Gomes da Silva J.; Gómez Zazo L.J.; Gomez-Lopez J.M.; González Hernández J.I.; Gonzalez Murillo K.; Gonzalo Melchor A.; Gorius N.; Gouel P.-V.; Goulty D.; Granata V.; Grenfell J.L.; Grießbach D.; Grolleau E.; Grouffal S.; Grziwa S.; Guarcello M.G.; Gueguen L.; Guenther E.W.; Guilhem T.; Guillerot L.; Guillot T.; Guiot P.; Guterman P.; Gutiérrez A.; Gutiérrez-Canales F.; Hagelberg J.; Haldemann J.; Hall C.; Handberg R.; Harrison I.; Harrison D.L.; Hasiba J.; Haswell C.A.; Hatalova P.; Hatzes A.; Haywood R.; Hébrard G.; Heckes F.; Heiter U.; Hekker S.; Heller R.; Helling C.; Helminiak K.; Hemsley S.; Heng K.; Herbst K.; Hermans A.; Hermes J.J.; Hidalgo Torres N.; Hinkel N.; Hobbs D.; Hodgkin S.; Hofmann K.; Hojjatpanah S.; Houdek G.; Huber D.; Huesler J.; Hui-Bon-Hoa A.; Huygen R.; Huynh D.-D.; Iro N.; Irwin J.; Irwin M.; Izidoro A.; Jacquinod S.; Jannsen N.E.; Janson M.; Jeszenszky H.; Jiang C.; Jimenez Mancebo A.J.; Jofre P.; Johansen A.; Johnston C.; Jones G.; Kallinger T.; Kálmán S.; Kanitz T.; Karjalainen M.; Karjalainen R.; Karoff C.; Kawaler S.; Kawata D.; Keereman A.; Keiderling D.; Kennedy T.; Kenworthy M.; Kerschbaum F.; Kidger M.; Kiefer F.; Kintziger C.; Kislyakova K.; Kiss L.; Klagyivik P.; Klahr H.; Klevas J.; Kochukhov O.; Köhler U.; Kolb U.; Koncz A.; Korth J.; Kostogryz N.; Kovács G.; Kovács J.; Kozhura O.; Krivova N.; Kuĉinskas A.; Kuhlemann I.; Kupka F.; Laauwen W.; Labiano A.; Lagarde N.; Laget P.; Laky G.; Lam K.W.F.; Lambrechts M.; Lammer H.; Lanza A.F.; Lanzafame A.; Lares Martiz M.; Laskar J.; Latter H.; Lavanant T.; Lawrenson A.; Lazzoni C.; Lebre A.; Lebreton Y.; Lecavelier des Etangs A.; Lee K.; Leinhardt Z.; Leleu A.; Lendl M.; Leto G.; Levillain Y.; Libert A.-S.; Lichtenberg T.; Ligi R.; Lignieres F.; Lillo-Box J.; Linsky J.; Liu J.S.; Loidolt D.; Longval Y.; Lopes I.; Lorenzani A.; Ludwig H.-G.; Lund M.; Lundkvist M.S.; Luri X.; Maceroni C.; Madden S.; Madhusudhan N.; Maggio A.; Magliano C.; Magrin D.; Mahy L.; Maibaum O.; Malac-Allain L.; Malapert J.-C.; Malavolta L.; Maldonado J.; Mamonova E.; Manchon L.; Manjón A.; Mann A.; Mantovan G.; Marafatto L.; Marconi M.; Mardling R.; Marigo P.; Marinoni S.; Marques R.; Marques J.P.; Marrese P.M.; Marshall D.; Martínez Perales S.; Mary D.; Marzari F.; Masana E.; Mascher A.; Mathis S.; Mathur S.; Martín Vodopivec I.; Mattiuci Figueiredo A.C.; Maxted P.F.L.; Mazeh T.; Mazevet S.; Mazzei F.; McCormac J.; McMillan P.; Menou L.; Merle T.; Meru F.; Mesa D.; Messina S.; Mészáros S.; Meunier N.; Meunier J.-C.; Micela G.; Michaelis H.; Michel E.; Michielsen M.; Michtchenko T.; Miglio A.; Miguel Y.; Milligan D.; Mirouh G.; Mitchell M.; Moedas N.; Molendini F.; Molnár L.; Mombarg J.; Montalban J.; Montalto M.; Monteiro M.J.P.F.G.; Montoro Sánchez F.; Morales J.C.; Morales-Calderon M.; Morbidelli A.; Mordasini C.; Moreau C.; Morel T.; Morello G.; Morin J.; Mortier A.; Mosser B.; Mourard D.; Mousis O.; Moutou C.; Mowlavi N.; Moya A.; Muehlmann P.; Muirhead P.; Munari M.; Musella I.; Mustill A.J.; Nardetto N.; Nardiello D.; Narita N.; Nascimbeni V.; Nash A.; Neiner C.; Nelson R.P.; Nettelmann N.; Nicolini G.; Nielsen M.; Niemi S.-M.; Noack L.; Noels-Grotsch A.; Noll A.; Norazman A.; Norton A.J.; Nsamba B.; Ofir A.; Ogilvie G.; Olander T.; Olivetto C.; Olofsson G.; Ong J.; Ortolani S.; Oshagh M.; Ottacher H.; Ottensamer R.; Ouazzani R.-M.; Paardekooper S.-J.; Pace E.; Pajas M.; Palacios A.; Palandri G.; Palle E.; Paproth C.; Parro V.; Parviainen H.; Pascual Granado J.; Passegger V.M.; Pastor-Morales C.; Pätzold M.; Pedersen M.G.; Pena Hidalgo D.; Pepe F.; Pereira F.; Persson C.M.; Pertenais M.; Peter G.; Petit A.C.; Petit P.; Pezzuto S.; Pichierri G.; Pietrinferni A.; Pinheiro F.; Pinsonneault M.; Plachy E.; Plasson P.; Plez B.; Poppenhaeger K.; Poretti E.; Portaluri E.; Portell J.; Porto de Mello G.F.; Poyatos J.; Pozuelos F.J.; Prada Moroni P.G.; Pricopi D.; Prisinzano L.; Quade M.; Quirrenbach A.; Rabanal Reina J.A.; Rabello Soares M.C.; Raimondo G.; Rainer M.; Ramón Rodón J.; Ramón-Ballesta A.; Ramos Zapata G.; Rätz S.; Rauterberg C.; Redman B.; Redmer R.; Reese D.; Regibo S.; Reiners A.; Reinhold T.; Renie C.; Ribas I.; Ribeiro S.; Ricciardi T.P.; Rice K.; Richard O.; Riello M.; Rieutord M.; Ripepi V.; Rixon G.; Rockstein S.; Rodón Ortiz J.R.; Rodrigo Rodríguez M.T.; Rodríguez Amor A.; Rodríguez Díaz L.F.; Rodriguez Garcia J.P.; Rodriguez-Gomez J.; Roehlly Y.; Roig F.; Rojas-Ayala B.; Rolf T.; Rørsted J.L.; Rosado H.; Rosotti G.; Roth O.; Roth M.; Rousseau A.; Roxburgh I.; Roy F.; Royer P.; Ruane K.; Rufini Mastropasqua S.; Ruiz de Galarreta C.; Russi A.; Saar S.; Saillenfest M.; Salaris M.; Salmon S.; Saltas I.; Samadi R.; Samadi A.; Samra D.; Sanches da Silva T.; Sánchez Carrasco M.A.; Santerne A.; Santiago Pé A.; Santoli F.; Santos Ä.R.G.; Sanz Mesa R.; Sarro L.M.; Scandariato G.; Schäfer M.; Schlafly E.; Schmider F.-X.; Schneider J.; Schou J.; Schunker H.; Schwarzkopf G.J.; Serenelli A.; Seynaeve D.; Shan Y.; Shapiro A.; Shipman R.; Sicilia D.; Sierra sanmartin M.A.; Sigot A.; Silliman K.; Silvotti R.; Simon A.E.; Simoyama Napoli R.; Skarka M.; Smalley B.; Smiljanic R.; Smit S.; Smith A.; Smith L.; Snellen I.; Sódor Á.; Sohl F.; Solanki S.K.; Sortino F.; Sousa S.; Southworth J.; Souto D.; Sozzetti A.; Stamatellos D.; Stassun K.; Steller M.; Stello D.; Stelzer B.; Stiebeler U.; Stokholm A.; Storelvmo T.; Strassmeier K.; Strøm P.A.; Strugarek A.; Sulis S.; Švanda M.; Szabados L.; Szabó R.; Szabó G.M.; Szuszkiewicz E.; Talens G.J.; Teti D.; Theisen T.; Thévenin F.; Thoul A.; Tiphene D.; Titz-Weider R.; Tkachenko A.; Tomecki D.; Tonfat J.; Tosi N.; Trampedach R.; Traven G.; Triaud A.; Trønnes R.; Tsantaki M.; Tschentscher M.; Turin A.; Tvaruzka A.; Ulmer B.; Ulmer-Moll S.; Ulusoy C.; Umbriaco G.; Valencia D.; Valentini M.; Valio A.; Valverde Guijarro Á.L.; Van Eylen V.; Van Grootel V.; van Kempen T.A.; Van Reeth T.; Van Zelst I.; Vandenbussche B.; Vasiliou K.; Vasilyev V.; Vaz de Mascarenhas D.; Vazan A.; Vela Nunez M.; Velloso E.N.; Ventura R.; Ventura P.; Venturini J.; Vera Trallero I.; Veras D.; Verdugo E.; Verma K.; Vibert D.; Vicanek Martinez T.; Vida K.; Vigan A.; Villacorta A.; Villaver E.; Villaverde Aparicio M.; Viotto V.; Vorobyov E.; Vorontsov S.; Wagner F.W.; Walton N.; Walton D.; Wang H.; Waters R.; Watson C.; Wedemeyer S.; Weeks A.; Weingrill J.; Weiss A.; Wendler B.; West R.; Westerdorff K.; Westphal P.-A.; Wheatley P.; White T.; Whittaker A.; Wickhusen K.; Wilson T.; Windsor J.; Winter O.; Winther M.L.; Winton A.; Witteck U.; Witzke V.; Woitke P.; Wolter D.; Wuchterl G.; Wyatt M.; Yang D.; Yu J.; Zanmar Sanchez R.; Zapatero Osorio M.R.; Zechmeister M.; Zhou Y.; Ziemke C.; Zwintz K.; Böhm T.; Dansac L.M. (My University, 2025)
PLATO (PLAnetary Transits and Oscillations of stars) is ESA’s M3 mission designed to detect and characterise extrasolar planets and perform asteroseismic monitoring of a large number of stars. PLATO will detect small planets (down to <2REarth) around bright stars (<11 mag), including terrestrial planets in the habitable zone of solar-like stars. With the complement of radial velocity observations from the ground, planets will be characterised for their radius, mass, and age with high accuracy (5%, 10%, 10% for an Earth-Sun combination respectively). PLATO will provide us with a large-scale catalogue of well-characterised small planets up to intermediate orbital periods, relevant for a meaningful comparison to planet formation theories and to better understand planet evolution. It will make possible comparative exoplanetology to place our Solar System planets in a broader context. In parallel, PLATO will study (host) stars using asteroseismology, allowing us to determine the stellar properties with high accuracy, substantially enhancing our knowledge of stellar structure and evolution. The payload instrument consists of 26 cameras with 12cm aperture each. For at least four years, the mission will perform high-precision photometric measurements. Here we review the science objectives, present PLATO‘s target samples and fields, provide an overview of expected core science performance as well as a description of the instrument and the mission profile towards the end of the serial production of the flight cameras. PLATO is scheduled for a launch date end 2026. This overview therefore provides a summary of the mission to the community in preparation of the upcoming operational phases. © The Author(s) 2025.